Bias-assisted atomic force microscope nanolithography on NbS2 thin films grown by chemical vapor deposition. (4th November 2016) - Bark, Hunyoung; Kwon, Sanghyuk; Lee, Changgu
Abstract: Niobium disulfide, one of the metallic transition metal dichalcogenides, has a high potential as an electrode material for electronic devices made of 2D materials. Here, we investigated the bias-assisted atomic force microscope nanolithography of NbS2 thin films synthesized by chemical vapor deposition. We analyzed the lithographed pattern using Raman spectroscopy, transmission electron microscopy and friction force microscopy. These analyses showed that lines having various widths and thicknesses could be generated using the lithography technique by simply varying the scan speed and applied voltage. These analyses also revealed that the NbS2 film transformed from a layered crystalline structure into an amorphous structure upon being lithographed. By generating four line segments forming a square and measuring I/V curves inside and outside of the square, the electrical properties of the lithographed material were characterized. These analyses indicate that NbS2 became hydrogenated and an insulator upon being lithographed.